KAPASITAS TNI AD DALAM PENANGGULANGAN BENCANA ALAM STUDI KASUS: KAPASITAS KODIM 0505/JAKARTA TIMUR DALAM PENANGGULANGAN BENCANA BANJIR - Patria, Reza Nur (Jurnal Pertahanan & Bela Negara, 2013)
This essay discusses the capacity of the army in response to natural disasters. The focus in this study is the readiness of Army personnel in carrying out duties on natural disaster emergency response phase. Personnel as one of the most important elements of the army capacity is playing the most important role in the achievement of the tasks. With a limited defense budget that is focused specifically in the task of MOOTW, capacity building of personnel is one way to increase the role of the TNI particularly the Army in carrying out the task of natural disaster.Â Keywords: capacity, training & education, core competence, flood disaster